Indirect Effects of Extracurricular Participation on Academic Adjustment Via Perceived Friends' Prosocial Norms. - Hughes, Jan; Cao, Qian; Kwok, Oi-man (Journal of Youth & Adolescence, 2016)
Students who participate in extracurricular activities in middle school exhibit higher levels of academic motivation and achievement, including graduation from high school. However, the mechanisms responsible for these beneficial effects are poorly understood. Guided by the bioecological models of development, this study tested the indirect effects of participation in grade 8 in school sports or performance arts and clubs on grade 9 academic achievement, academic competence beliefs, and school belonging, via adolescents' perceptions of their friends' prosocial norms. Participants were 495 (45 % female) ethnically diverse students (mean age at grade 8 = 13.9 years; SD = .58) who were recruited into a longitudinal study on the basis of below average literacy in grade 1. Using weighted propensity score analyses to control for potential confounders, results of longitudinal SEM found indirect effect of participation in sports, but not of participation in performance arts and clubs, on grade 9 outcomes noted above. Implications of findings for improving educational attainment of at-risk youth are discussed.